Multidimensional tax compliance attitude - Christoffer Bruns; Martin Fochmann; Peter N. C. Mohr; Benno Torgler (Freie Universität Berlin, School of Business & Economics, 2023)
Citizen tax compliance significantly dictates governmental fiscal capacities. Recognizing this, understanding the determinants of tax compliance remains paramount. While existing literature frequently isolates and tests individual determinants such as audit likelihood, penalty structures, tax morale, and perceived fairness, an integrative, bottom-up approach addressing the spectrum of tax compliance attitudes has largely been overlooked. Addressing this gap, our study constructs a multidimensional Tax Compliance Attitude Inventory (TCAI) by harmonizing real taxpayer responses with established theoretical underpinnings. Through factor analysis, we delineate four pivotal factors: (i) morale, (ii) monetary benefit, (iii) deterrence, and (iv) authority. Notably, morale and deterrence emerge as consistent influencers of tax compliance. Embracing this multidimensionality, our cluster analysis demarcates two distinct taxpayer personas: (a) moralists and (b) rationalists. Our findings underscore that moralists consistently exhibit higher tax compliance than their rationalist counterparts. We further present a streamlined classification algorithm to operationalize the TCAI in new datasets, minimizing item count. This work serves as a seminal contribution, offering both academia and tax authorities a robust, quantitative tool to gauge tax compliance attitudes.
urn:nbn:de:kobv:188-refubium-41152-7
Keywords: C38; C83; D91; H26; 330; Behavioral economics; compliance attitudes; compliance behavior; tax evasion; heterogeneous individuals